Canine Parvovirus in Dogs - Sendow, Indrawati (Indonesian Bulletin of Animal and Veterinary Sciences, 2003)
Parvovirus disease in dogs is caused by Parvovirus, a member of famili Parvoviridae. In young puppies, less than 4 months age, CPV infect heart, while older puppies CPV will infect tractus digestivus, which caused blood diarrhoea. In general, the cinical signs of CPV disease are vomit, loss appetite, and blood diarrhoea. Parvovirus will inactivated by given chemical reagents such as Hypoclorised or formalin. Vaccination is the only way to protect the disease. The right time of vaccination will give the optimum protection of the disease. Hence, monitoring the immune response after vaccination needs to be developed to gain the information on the best time to vvaccinate the dogs, so the failure of vaccination can be avoided. Â  Key words: Parvovirus, vaccination, diagnosis